Determinants of Self-Medication Practices among Nursing and Midwifery Students: A Cross-Sectional Study from Ghana - Opoku, Oscar Agyemang; Agyiriba, Juliet; Okudzeto, Henry (Chakra Brahmanda Lentera Institute, 2025)
Background: Self-medication is a growing public health concern, particularly among healthcare students. Despite its risks, including adverse drug reactions and antibiotic resistance, little is known about the behavioral and socioeconomic factors influencing self-medication among nursing and midwifery students in sub-Saharan Africa. This study assessed the prevalence and determinants of self-medication among students at the Nursing and Midwifery Training College in Koforidua, Ghana. Methods: A cross-sectional quantitative design was adopted, involving 275 students selected through stratified random sampling. Data were collected using a structured and pretested questionnaire covering demographic characteristics, knowledge, and self-medication practices. Descriptive statistics were performed using SPSS version 26 to summarize frequencies and percentages related to knowledge, behavior, and influencing factors. Results: Self-medication was highly prevalent (94.3%) among respondents, with painkillers (52.2%), cold and flu medications (22.6%), and antibiotics (20.0%) being the most commonly used drugs. The main factors influencing self-medication were time constraints (91.7%), financial barriers (81.3%), family history (53.9%), and advice from friends or relatives (87.8%). Although 91.8% of respondents recognized the risks associated with self-medication, many continued the practice due to perceived convenience and cost-saving benefits. Conclusion: Self-medication is widespread among nursing and midwifery students in Ghana, primarily driven by financial and time constraints as well as social influences. Educational interventions and institutional policies promoting rational drug use are urgently needed. Collaboration between nursing schools and the Ghana Health Service could enhance awareness and ensure responsible self-care behaviors among future healthcare professionals.